The outcomes of digital tip amputation replacement as a composite graft in a paediatric population. (February 2016) - Butler, D. P.; Murugesan, L.; Ruston, J.; Woollard, A. C.; Jemec, B.
Limited studies exist on the outcome of replacing an amputated fingertip as a composite graft. We report the outcomes and predictors for composite graft survival along with the long-term morbidity. A retrospective review of all patients <16 years who underwent composite graft replacement of an amputated fingertip was performed. Long-term morbidity was evaluated through a standardized parental questionnaire. A total of 120 patients were identified, of whom 97 were eligible for inclusion. Parental questionnaires were completed for 42 (43%) patients. There was a 10% complete and 34% partial graft survival rate. Patients aged ⩽4 were significantly more likely to have complete graft take than those >4. Of the patients, 17% developed post-operative complications; 48% of patients reported a hook-nail deformity and 17% reported cold intolerance. Only 5% of patients reported any functional difficulties long term. The rate of complete composite graft survival in a paediatric population is low, although the long-term function of these patients is good. Level of evidence: 3